Effect of the Diffusion Bonding Conditions on Joints Strength - D. Kadhim, Zeyad; I. Al- Azzawi, Ali; J. Al-Janabi, Sabah (Journal of Engineering and Sustainable Development, 2009)
In this research the effect of different parameters on the strength of joints which bonded by using diffusion bonding process has been studied. The specimens of copper and nickel were annealed in a vacuum furnace at (800 ºC). Specimens of Cu and Ni were plastically deformed to (0%, 10%, 20%, and 30%) in tension before diffusion bonding process. Diffusion bonding was carried out at different conditions (temperatures, pressures, periods of the time, and surface roughness of the mating surface).The parts were diffusion bonded using a creep machine with a jig in a vacuum chamber flushed with argon gas after evacuation to about 10-² torr to prevent oxidation. It has been found that the strength of bonded joints increased with increasing the parameters (temperature, pressure, and time of diffusion bonding). This increment of joint strength is just for a certain value and then decreased with increasing the pervious parameters.Besides that it has been found that the bonded joint strength decreases with increasing the roughness of the mating surface. Furthermore the bonded joint strength increased with increasing the percentage of plastic deformation of specimens before diffusion bonding process